Analisis Impementasi Pinjaman Tanpa Jaminan pada Baznas Provinsi Sumatera Utara untuk Pengembangan Usaha Pedagang Kaki Lima - Eka Adinda Salshabilla; Syahrul Amsari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim of analyzing the problematic settlement of unsecured financing, the factors that cause the weakness of the unsecured loan system and minimize the risks that occur in unsecured financing applied by BAZNAS of North Sumatra Province. In this study, qualitative research was carried out which consisted of interviews, observation and documentation. The results of the research were obtained in solving problematic unsecured loan financing, namely by extending the loan period, extending the installment period or changing the amount of installments. The factors that cause the weakness of this unsecured loan system is the internal factor which lacks thoroughness in checking the authenticity of documents and the ease of providing loans to customers. In minimizing the risks that occur in unsecured loans, namely rescheduling installment payments or repayments that have been taken by the customer, rearranging and rearranging the conditions contained in the terms of the unsecured loans provided by BAZNAS North Sumatra and the process of rearranging loan / credit conditions involving the borrower in question to ease the loan repayment process. Keywords: Problematic Financing, Weak Loan System, Risk